Islamic Business Ethics - Jie, Li; Jixiong, Cai; Wei, Zhang (Sharia Oikonomia Law Journal, 2023)
The purpose of writing this article is to increase knowledge and can be used as a reference to add references related to the topic presented, namely Business Ethics in Islam. The method used is a qualitative method using a literature study approach. In researching this article, the author conducted a literature study by looking for various written sources such as books, archives, articles, scientific journals, and documents that are relevant to the discussion being discussed, namely business ethics in an Islamic perspective. Supporting activities carried out to determine the literature review in this study include reading, searching, and analyzing expert opinions and library materials that contain theories related to the discussion articles. Ethics in business is very necessary for an entrepreneur in running his business. In Islam it has also been explained that ethics is one of the important things and is very helpful in improving the performance of a business as exemplified by the Prophet Muhammad SAW. Therefore, as Muslims are required to apply Islamic business ethics in doing business.